The Effect Of Using Different Liquids On The Organoleptic Quality Of Donuts - Mailisa, Ratu; Faridah, Anni; Elida, Elida; Anggraini, Ezi (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Donuts are a processed product made from Cakra wheat flour, produced by frying after the dough has been fermented. The liquids used in the donut-making process, such as mineral water, coconut water, and sugarcane juice, play a crucial role in determining the quality of the donuts.This study aimed to determine the effect of different liquid additions on donut quality, including the parameters of volume, color, aroma, texture, and taste. The liquids used were mineral water (X0), coconut water (X1), and sugarcane juice (X2). The experiment was conducted using a completely randomized design (CRD) with three treatments and three replications. Sensory evaluation was performed by 30 panelists using a hedonic scale, and the data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test when significant differences were found. The results showed that the type of liquid used significantly affected several sensory quality parameters of donuts. The volume parameter had mean values of X0 = 5.37, X1 = 5.56, and X2 = 4.68, with Fcount 3.34 > Ftable 3.16, indicating a significant difference. The color parameter had mean values of X0 = 5.48, X1 = 5.91, and X2 = 5.72, but Fcount 2.87 < Ftable 3.16, indicating no significant difference. For aroma, the mean values were X0 = 3.97, X1 = 4.81, and X2 = 5.86, with Fcount 3.97 > Ftable 3.16, showing a significant difference among treatments. The texture parameter recorded X0 = 5.53, X1 = 6.17, and X2 = 4.58, with Fcount 3.73 > Ftable 3.16, also indicating a significant difference. Meanwhile, the taste parameter had mean values of X0 = 5.30, X1 = 5.27, and X2 = 5.49, with Fcount 2.90 < Ftable 3.16, meaning no significant difference was found. Overall, coconut water (X1) produced the best volume and texture quality, while sugarcane juice (X2) resulted in the most preferred aroma and taste by panelists. The use of two types of natural liquids, namaly old coconut water and sugar cane water in making donuts, greatly affects the quality of the donuts.